Proses simulasi- simulakra-hiperealitas dalam majelis taklim jn Surabaya - Dwi Retnani Srinarwati (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
The Taklim Council carries out a series of activities that are believed to be a way to emigrate, change, and transform in order to improve themselves by getting closer to the Creator. By attending one of the recitations at the JN Surabaya Taklim Council, the congregation also participated in the transformation. The purpose of this study was to determine the simulacra-simulation-hypereality process in the JN Surabaya Taklim Council. This study uses a descriptive qualitative approach that describes the process that researchers use to interpret the activities of the JN Surabaya Taklim Council and see the activities (events) from various angles. The results of this study indicate that the process of simulating the JN Surabaya Taklim Council has produced a new meaning for the congregation towards the Taklim Council itself, namely the meaning of Real value and Exit Value.